ENHANCING MATEMATICAL COMMUNICATION AND DISPOSITION ABILITIES THROUGH MODEL-ELICITING ACTIVITIES (MEAs) LEARNING - Yani Siti Tuadah Afriani; Siti Fatimah; Yaya Sukjaya Kusumah (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
The purpose of this study is to analyze the enhancement mathematical communication ability and the achievement mathematical disposition of junior high school students under Model-Eliciting Activities (MEAs) learning. This study was a quasi-eperimental in one of the junior high schools in Bandung, with the design of non-equivalent control group involving 80 students of grade VII. The instrument used for measuring students ability was a test on mathematical communication, whereas for measuring their mathematical disposition, a questionaire was used . The statistical analysis performed were Mann-Whitney test, and one way ANOVA test. The research results obtained are: (1) the enhancement the students mathematical communication abilities who work under Model-Eliting Activities (MEAs) learning is better than the students who work under conventional learning, (2) there are differences in the improvement in mathematical communication ability between students who have mathematical prior knowledge (KAM) high, midlle, low, (3) the students achievement in mathematical disposition who work under Model-Eliciting Activities (MEAs) learning is better than those who work under conventional learning.